ANALISIS PELAKSANAAN MOTIVASI 10 MENIT TERHADAP MINAT BELAJAR MAHASISWA PROGRAM STUDI ADMINISTRASI BISNIS DI POLITEKNIK LP3I JAKARTA KAMPUS KRAMAT - Euis Winarti (POLITEKNIK LP3I JAKARTA, 2018)
ABSTRACT This research is intended to analyze the implementation of 10 minutes motivation to influence the interest of the students of Business Administration Program Polytechnic LP3I Jakarta. The research population is all students of Academic Year Academic Year study program 2017/2018 which amounted to 105 people, and sampling technique used is purposive sampling with a sample of 40 students. From the result of the research, it is found that 10 min (X) has a significant influence on student learning interest (Y) where the correlation coefficient is 0.376 or equal to 37.6% (strong enough). Keywords: motivation, interest in student learning